Does internet expansion matter for export concentration? - Nguyen-Quoc Thang (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
Why do export sales increasingly concentrate among a few "superstars"? This paper is the first to argue that the expansion of the Internet matters for this phenomenon. Using firm-level customs transaction data from 11 developing countries, we show that the spread of the internet steepens the slope of the rank-sales relationship among exporters. This shift implies a more skewed distribution of sales toward the top exporters. Furthermore, incumbent superstar exporters are more likely to retain their status owing to a better Internet. Doubling internet adoption is expected to boost the chance for the incumbent top exporter to retain its top position by 11.7%. This boost suggests an "entrenchment" effect where the internet reduces churning at the top. For both findings, we find some evidence that the effects are stronger for exports of differentiated goods than for exports of homogenous goods, suggesting the role of information friction in explaining the results. These findings suggest that the expansion of the Internet, and the broader digitalisation process, is a contributing factor to the increasing concentration of exports among a few "superstars". As digitalisation continues, macroeconomic policymakers will need to step up their monitoring of idyosyncractic shocks related to these "superstars". Policymakers also need to adapt their trade and development strategy in light of the shifting competitiveness landscape created by digitalisation. As the competition structure in the internet era favours superstars, the focus of export-promotion strategies may need to shift from supporting export entrepreneurship to enhancing the linkages between export superstars and domestic suppliers.
hdl:20.500.12870/6807
Keywords: D22; L25; L86; F14; 330; firm size distribution; export superstars; internet; digitalisation